Artificial intelligence's new frontier. (Economist, 2022)
The article focuses on the foundation models that represents breakthrough in artificial intelligence (AI) and mentions consideration of the models as twist on deep learning. Topics discussed include binary computational decisions fused into human creativity and comprehension, threat possessed to people by the AI-powered automation and rules for manipulating computer programming.